Buffaloes’ clinico-pathological responses to Pasteurella multocida type B:2 and their immunogens lipopolysaccharide and outer membrane protein - Lim, Eric Teik Chung (2016)
Sudden death is usually the main finding in field during haemorrhagic septicaemia (HS) outbreaks among livestock in Malaysia. HS is an acute fatal disease, caused by particular serotypes of Pasteurella multocida. Epidemic haemorrhagic septicaemia in Asian countries including Malaysia is caused by P. multocida serotype B:2. This organism causes acute, highly fatal septicaemia with high morbidity and mortality in cattle and more susceptible in buffaloes. P. multocida is a gram negative, short, ovoid, bipolar staining coccoid forms. It is an extracellular parasite, and immunity is primarily humoral. In most cases, the clinical findings are either acute or peracute, resulting death within 8 to 24 hours after onset. The two immunogens of wild-type Pasteurella multocida that have the virulence factors are the outer membrane protein (OMP) and lipopolysaccharide (LPS). Little is known about the effect of endotoxin of P. multocida type B:2 and its immunogens LPS and OMP towards host cell responses in buffaloes. Thus, this study was designed to investigate the clinico-pathology, haemato- biochemistry changes, the acute phase responses (APP), antibody titres and cytokine concentrations in buffaloes infected by P. multocida type B:2 and its immunogens. A total of twenty one buffalo heifers were divided equally into 7 treatment groups. Group 1 was inoculated orally with 10 mL of phosphate buffer saline (PBS) as negative control; Groups 2 and 3 were infected with 10 mL of 1012 colony forming unit (cfu) P. multocida type B:2 subcutaneously and orally respectively; Groups 4 and 5 were inoculated with 10 mL of LPS broth intravenously and orally respectively; and OMP broth were inoculated subcutaneously and orally into Groups 6 and 7 buffaloes respectively. During the post infection period, all the buffaloes were observed for clinical signs and clinical response for 21 days. Blood samples were also collected throughout the 21 days for determination of blood and biochemistry changes, concentration of proinflammatory cytokines, APP and antibody titres. At the end of the study, buffaloes that exhibited typical HS signs and buffaloes that survived throughout the 21 days study period were euthanized for post mortem and histopathological examination. All buffaloes from Groups 1, 3, 4, 5, and 7 were able to survive throughout the stipulated experimental period of 21 days. Group 2 and 6 buffaloes were only able to survive for 12 hours and 3 days respectively. Group 2 buffaloes showed severe HS clinical responses and were only able to survive for 12 hours post infection. The blood and biochemistry results showed erythrocytosis, leukopaenia, neutropaenia and lymphopaenia. All vital organs, gastrointestinal and immune organs were severely affected with severe histopathology lesions. However, Group 3 buffaloes were able to survive throughout the experiment for 21 days despite showing mild clinical responses that only lasted for 4 days. The blood and biochemistry results showed leukocytosis for the first 5 days. Only the lung and liver organs were moderately affected with moderate histopathology lesions. On the other hand, Group 4 buffaloes demonstrated mild clinical responses and survived throughout the stipulated time of 21 days. All buffaloes had leukocytosis, lymphocytosis and monocytosis throughout 21 days experiment. All vital organs, gastrointestinal and immune organs were moderately affected with mild histopathology lesions. Similarly, Group 5 buffaloes demonstrated very mild clinical responses and able to survive for 21 days. Leukocytosis, monocytosis and eosinophilia were observed in this buffalo group. Only the lung and liver had mild gross lesions. Besides, mild histopathology findings were observed in all organs. Similar to Group 2, Group 6 buffaloes also exhibited severe HS clinical responses and were only able to survive for 72 hours post infection. The blood and biochemistry results showed monocytosis and elevated gamma glutamyl transferase (GGT) during the first 72 hours of the experiment prior euthanasia. All vital organs, gastrointestinal and immune organs were severely affected with moderate histopathology changes. In contrast, there were no significant clinical responses in Group 7 buffaloes. All buffaloes only had monocytosis throughout the 21 days of experiment. Gross lesions were only observed in the lung and liver of Group 3 buffaloes with moderate histopathological lesions. Buffaloes in all treatment groups of P. multocida type B:2 and its immunogens LPS and OMP showed significant increase in haptoglobin (Hp) and serum amyloid A (SAA) concentrations throughout the study period. There were significant differences (p<0.05) in all treatment groups compared to control group of buffaloes. In addition, buffaloes in all treatment groups showed significant increase in IgM, IgG and IgA concentrations throughout the study period. There were significant different (p<0.05) in all treatment groups compared to control group. Similarly, all treatment groups showed significant increase (p<0.05) in IL-2 and IL-6 concentration; but no significant difference (p>0.05) in IL-12 concentration observed compared to control group. Therefore, from the present study, it can be concluded that buffaloes infected with P. multocida type B:2 and its immunogens LPS and OMP demonstrated different host cell responses. Information on this will play a significant role in understanding the host cell response during HS outbreaks. Buffaloes inoculated orally with OMP demonstrated as a promising candidate to be developed into oral vaccine based on the clinical response, haemato-biochemistry, gross lesion, histopathology finding, and most importantly antibody level. With this, alternative route for HS where oral route of vaccination can be considered compared to intramuscular route in future. Besides that, the development of biomarkers using cytokines in future will be able to control the outbreak of HS which causes major losses with great economic impact to the country.